Studies on properties of Molybdenum filed Polypropylene composites - Azlin Fazlina, Osman; Junizah A.R. (Institut Teknologi Brunei, 2009)
Organized by Institut Teknologi Brunei(ITB), 3rd - 4th November 2008 at Rizqun International Hotel, Brunei.